Puberty in Crioula Lageana breed heifers - Giacomini, Karyna (2020)
Age of puberty was evaluated in heifers (Crioula Lageana Breed) submitted to two post-weaning feeding systems, in the Santa Catarina Plateaus, Brazil. This study was composed of: Treatment I, in which nine animals were maintained in cultivated pasture during the winter, and Treatment II, in which nine animals were maintained in natural pastures during the whole period of the experiment. In both treatments, animals received mineral supplementation. Daily observations of estrus behavior were made. All animals were submitted to rectal palpation and ultrasound exam; blood samples were taken weekly and all the animals were weighed monthly. Puberty was characterized by the first estrus, with or without oestrus behavior, confirmed by the formation of the corpus luteum and plasmatic concentrations of progesterone by radioimmunoassay (RIA) over 1ng/ml, in two consecutive samples.Using cultivated pastures for Crioula Lageana heifers after weaning, in the winter, advanced their age of puberty. The results showed that 15-month-old animals weighing approximately 300kg are ready for reproduction.